Uso de recursos polínicos e conteúdo proteico do pólen na dieta de abelhas Meliponinae (Apidae: Hymenoptera) na região do Alto Uruguai, Brasil - Bueno, Alana da Cruz (2018)
The stingless bee (Apidae: Meliponinae) are found, for the most part, in the neotropical region. This work aims to analyze and identify the pollens of the pollen reserves to know the floral preferences of five species of stingless bees, Nannotrigona testaceicornis Lepeletier, 1836, Melipona quadrifasciata Lepeletier, 1836. Melipona marginata Moure, 1971, Tetragonisca angustula Schwarz, 1938 e Scaptotrigona depilis Moure, 1942. It also deals with the protein analysis of pollen that showed the highest floral preference of three species of bees, T. angustula, M. q. quadrifasciata e S. depilis, with the aim of knowing whether or not the floral preference is due to the protein value of the pollen. For pollen identification analyzes, the collections of the pollen reserves were carried out between September 2016 and March 2017 in the municipality of Barão de Cotegipe/RS, and analyzed in the laboratories of the Federal University of Southern Frontier (UFFS), campus of Erechim/RS and Chapecó/SC. The methodology used was adapted from J. Louveaux et al., and the pollen identification was performed from articles and catalogs on pollen morphology. The relative frequency and Shannon index (H ') were calculated to verify the pollen diversity, and the Pielou index (J') to verify the fairness of the samples. For the protein analyzes, the pollen was analyzed, that is, the pollen collected directly from the flower. The analysis of the pollen content interference in the pollen preference was carried out on the basis of pollen M. quadrifasciata, T. angustula and Scaptotrigona depilis, obtained between 2015 and 2016 in previous work, thus independent in the pollen analysis obtained in the present sampling. For the bee N. testaceicornis, the pollen diversity was 39 species and the species Eucalyptus tereticornis was predominant (17,04%); M. q. quadrifasciata presented 36 species with predominance of Morus sp., with 13.9%; M. marginata presented 30 species with Solanum sp. with 18.0%; T. angustula, 34 species, with predominance of Tibouchina mutabilis, with 24.66% and S. depilis, 35 species, with predominance of Tibouchina mutabilis with 28.90%. The month that presented the greatest diversity was the month of January, 2017, for the species M. marginata, com H’= 3,23 and greater equity, It was November 2016, for the same bee species, with J '= 0.96. Fourteen species with more floral preference were chosen for the three species of bees, collected at the UFFS campus Chapecó and in the municipality of Guatambu/SC, and protein analysis was performed according to the Bradford Method. E. tereticornis (with 32.25% protein) was the preference of M. quadrifasciata (34.9%); Syagrus (24.17% protein) of S. depilis (29.33%) and Mimosa scabrella (9.24% protein) for T. angustula (21.30%). M. quadrifasciata is the largest bee, compared to the others in this research, and prefers flowers with higher protein values.